Did COVID-19 Deteriorate Mismatch in the Japanese Labor Market? - Yudai Higashi; Masaru Sasaki (Institute of Labor Economics (IZA), 2023)
This study explores how the COVID-19 pandemic deteriorated the mismatch in the Japanese labor market. We first focus on differences in job flows and reservation wages by occupation and employment type, which differ according to the risk of infection. We next estimate the mismatch indices for local labor markets clustered in by occupations vulnerable and not vulnerable to COVID-19 using the method developed by Şahin et al. (2014). We find that the pandemic induced an overall mismatch, regardless of whether the occupations were vulnerable to infection. The mismatch for high-risk occupations was gradually eliminated in 2021, suggesting that the Japanese labor market adapted gradually but successfully to the new normal. However, the mismatch for low-risk occupations increased in 2021, indicating that labor mobility had been discouraged.
Keywords: J61; J62; J63; 330; mismatch; O-NET data; COVID-19; labor market tightness; desired wage